Trends and disparities in the US colorectal cancer mortality, 1999–2023: an analysis of the CDC WONDER database - Feng, Yingkai; Fa, Xinyu; Liu, Jianping; Qi, Hong (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) remains the second leading cause of cancer-related death in the USA. This study systematically assessed the spatiotemporal evolution of CRC mortality from 1999 to 2023 and explored sociodemographic and geographic disparities.MethodsDeath-certificate data for adults aged ≥ 25 years were extracted from the CDC WONDER database. CRC deaths were identified using ICD-10 codes C18–C20. Age-adjusted mortality rates (AAMR) were calculated with the 2000 US standard population. Stratified analyses were performed by age, sex, race/ethnicity, census region, state, and National Center for Health Statistics urban–rural classification. Joinpoint regression estimated annual percent change (APC) and average annual percent change (AAPC).ResultsAAMR rose annually by 0.45% in the 25–34-year group and 1.03% in the 35–44-year group but declined significantly among individuals ≥ 55 years (AAPC −1.43% to −3.20%). Adults ≥ 75 years accounted for more than half of CRC deaths. The South registered the highest AAMR (21.13 per 100,000), whereas the Northeast had the lowest (17.31 per 100,000). Non-Hispanic Black individuals experienced the highest AAMR (24.90 per 100,000). Nonmetropolitan counties showed higher AAMR (23.16 per 100,000) than metropolitan counties (18.69 per 100,000).ConclusionDespite an overall decline in US CRC mortality, rising risk among young adults and pronounced disparities across regions, racial/ethnic groups, and urban–rural settings persist. Targeted screening and intervention strategies for younger populations, high-burden areas, and vulnerable groups are essential to accelerate equitable reductions in CRC mortality.